2006
DOI: 10.1016/j.disc.2005.09.015
|View full text |Cite
|
Sign up to set email alerts
|

The metric dimension of Cayley digraphs

Abstract: A vertex x in a digraph D is said to resolve a pair u, v of vertices of D if the distance from u to x does not equal the distance from v to x. A set S of vertices of D is a resolving set for D if every pair of vertices of D is resolved by some vertex of S. The smallest cardinality of a resolving set for D, denoted by dim(D), is called the metric dimension for D. Sharp upper and lower bounds for the metric dimension of the Cayley digraphs Cay( : ), where is the group Z n 1 ⊕ Z n 2 ⊕ · · · ⊕ Z n m and is the can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 3 publications
0
72
0
Order By: Relevance
“…Figure 2 shows a resolving 3-partition Π = {P 1 , P 2 , P 3 } of V (D) (the vertices of D are labelled with their representations with respect to this 3-partition); so pd(D) ≤ 3. In [9] it was shown that dim(D) = 3, and hence, by Proposition 2.1, pd(D) ≥ 3.…”
Section: The Partition Dimension Of Cayley Digraphsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 shows a resolving 3-partition Π = {P 1 , P 2 , P 3 } of V (D) (the vertices of D are labelled with their representations with respect to this 3-partition); so pd(D) ≤ 3. In [9] it was shown that dim(D) = 3, and hence, by Proposition 2.1, pd(D) ≥ 3.…”
Section: The Partition Dimension Of Cayley Digraphsmentioning
confidence: 99%
“…The following result was established in [9]. is adjacent to a different vertex of P 2 in the underlying simple graph.…”
Section: It Can Be Shown Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…Some classes of graph whose metric dimension have been known are cycles [6], trees [5,8,10], stars [5,8,10], wheels [2,3,15], complete multipartite [5,14], unicylic graphs [12], Cayley graphs [7], and regular graphs [1].…”
Section: Introductionmentioning
confidence: 99%